2022
DOI: 10.1111/dme.14982
|View full text |Cite
|
Sign up to set email alerts
|

Advancing a causal role of type 2 diabetes and its components in developing macro‐ and microvascular complications via genetic studies

Abstract: The role of diabetes in developing microvascular and macrovascular complications has been subject to extensive research. Despite multiple observational and genetic studies, the causal inference of diabetes (and associated risk factors) on those complications remains incomplete. In this review, we focused on type 2 diabetes, as the major form of diabetes, and investigated the evidence of causality provided by observational and genetic studies. We found that genetic studies based on Mendelian randomization provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Several diabetes-related conditions contribute to increased cardiovascular risk. Among them, insulin resistance and hyperglycemia are the main drivers of atherothrombotic events leading to poor cardiovascular health [ 31 , 32 ]. Taking this into account, it is interesting to analyze the effect of beer intake on parameters related to glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Several diabetes-related conditions contribute to increased cardiovascular risk. Among them, insulin resistance and hyperglycemia are the main drivers of atherothrombotic events leading to poor cardiovascular health [ 31 , 32 ]. Taking this into account, it is interesting to analyze the effect of beer intake on parameters related to glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Two prior studies reported con icting results on the T2D-HF link. Mordi et al [28] (2021) found mediating variables slightly reduced the T2D-HF effect, while Ahmed et al [29] (2023) noted BMI and SBP nulli ed it. Our MR analysis reconciles these differences, con rming and bolstering the T2D-HF link based on recent evidence and extending past MR research.…”
Section: Principal Ndingsmentioning
confidence: 99%
“…Concerning weight management, a prior study [29] indicated that BMI mediate the relationship between T2D and HF. However, this association has limitations as individuals with similar BMIs may have differing metabolic and CVD risk pro les [35].…”
Section: Suggestions For Preventing Hf Complications In T2dmentioning
confidence: 99%
“…Rory McCrimmon, 9 this year's Dorothy Hodgkin Lecture recipient, has written an engaging overview of his prize lecture in which he has provided mechanistic insights into recurrent hypoglycaemia in diabetes. We are confident that the articles in this special issue, which are a mixture of primary research, 1–5,7 and state of the art reviews, 6,8,9 are accessible to non‐specialists and will be enjoyed by a wide readership.…”
mentioning
confidence: 98%
“…The most outstanding basic science diabetes researchers in the UK are awarded five‐year RD Lawrence Fellowships after competitive interview. Three of the current RD Lawrence Fellows (Benoit Hastoy and Quan Zhang 7 and Hanieh Yaghootkar 8 ) contributed articles that emphasise their expertise in the regulation of beta‐cell exocytosis 7 and genetic studies of vascular complications of diabetes 8 . The Diabetes UK Dorothy Hodgkin Lecture is awarded annually to internationally recognised basic science researchers in recognition of Hodgkin's achievement in determining the crystal structure of insulin.…”
mentioning
confidence: 99%